2009
DOI: 10.33899/edusj.2009.57680
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some substituted pyrimidines via cycloaddition reaction of amidines and chalcones

Abstract: Substituted amidines (1,2) where prepared from the condensation of benzyl, furfuryl alcohols and ethyl sulphate with thiourea. Chalcone compounds (3,5a and 5b) where also prepared from condensation of 4nitrobenzaldehyde to give compound (3) while acetophenone, 4-hydroxy benzaldehyde and 1,3-dibromopropane gave the diformyl intermediate (4) then it was underwent further reaction with either acetophenone or 4methyl acetophenone to afford compounds (5a,5b) respectively. Condensation of the above amidines with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Conversion was carried out from the ethynyl and azide absorption peak area (at 2030–2260 cm −1 ), which is reduced in accordance with the generated 1,2,3‐triazole network, compared to the sp 3 C‐H absorption peak area (at 2710–3045 cm −1 ), which does not change during the reaction, as shown in Figure . As reported, the C=C absorption peak of the triazole structure (at 1508–1558 cm −1 ) was also confirmed in our works, but this peak was very weak. For this reason, the triazole absorption peak was not used for the analysis of the conversion.…”
Section: Resultssupporting
confidence: 91%
“…Conversion was carried out from the ethynyl and azide absorption peak area (at 2030–2260 cm −1 ), which is reduced in accordance with the generated 1,2,3‐triazole network, compared to the sp 3 C‐H absorption peak area (at 2710–3045 cm −1 ), which does not change during the reaction, as shown in Figure . As reported, the C=C absorption peak of the triazole structure (at 1508–1558 cm −1 ) was also confirmed in our works, but this peak was very weak. For this reason, the triazole absorption peak was not used for the analysis of the conversion.…”
Section: Resultssupporting
confidence: 91%
“…The obtained IR bands match with those of unprotonated carbonyl and triazole groups and provide no evidence that protonation of the trans N]N group occurred. 54,56,57 This leads to the conclusion that the triglycerol head groups are the main protonation sites of trans 1 during nESI. Surprisingly, the ether and hydroxyl groups of the triglycerol head groups are associated with lower gas-phase basicity values than other building blocks (Table S3, ESI †).…”
Section: Switchable Protonation Sitesmentioning
confidence: 98%
“…4). 54,56,57 The structure of trans 1 offers multiple protonation sites, including the head groups, carbonyl groups, triazoles, and the N]N bond. The obtained IR bands match with those of unprotonated carbonyl and triazole groups and provide no evidence that protonation of the trans N]N group occurred.…”
Section: Switchable Protonation Sitesmentioning
confidence: 99%
“…Moreover, the SEM images showed the particle size to be $58 AE 21 nm. 158 Campos et al studied the experimental dental restorative composites and their development by the addition of montmorillonite (MMT) NPs in a polymer matrix-based BisGMA/ TEGDMA for assessing the feasibility of a distinct dimensional behavior during photo-polymerization. The researchers demonstrated that the experimental composites lled with MMT NP have statistically identical polymerization shrinkage values (by thermal mechanical analyses) at the concentration of 30% and less polymerization shrinkage values at the concentration of 50% than the composites that became full with barium glass (BG-control groups).…”
Section: Nano-materials For Restorationmentioning
confidence: 99%